Controle passivo de vibrações induzidas por vórtices utilizando materiais viscoelásticos - Cunha, Bruno Sousa Carneiro da (2016)
It is widely known that the vibrations induced by vortex shedding phenomena may have disastrous effects in engineering practice, affecting significantly the durability, reliability and safety of existing engineering structures. As an example, long cylindrical structures immersed in water that have performed well for decades have been recently found to have accumulated fatigue damage when subjected to vortex- induced vibrations, resulting in failure. This a reason for which in the last decades a great deal of effort has been devoted to the development of control strategies for dealing with the vortex-induced vibration of structures. However, surprisingly enough, few works have proposed the use of viscoelastic materials as a passive control strategy to suppress the undesirable vortex-induced vibrations, which motivates the study reported herein. In this paper, the Immersed Boundary Method combined with the Virtual Physical Model is used to investigate the dynamics of a viscoelastically mounted rigid circular cylinder in a fluid flow subjected to transverse vibrations induced by vortex shedding. It is suggested a straightforward time-domain modeling strategy of fluid- structure interactions systems incorporating viscoelastic materials by using a four- parameter fractional derivative model. After the theoretical aspects, numerical simulations are performed in order to evaluate the VIV response of a viscoelastically mounted circular cylinder in a fluid flow at a Reynolds number of 10000 for a range of reduced velocity and temperature of the viscoelastic material for two values of massratios. Through the obtained numerical results is it possible to verify the interest in using viscoelastic materials as an efficient passive control strategy of VIV problem.